Competitiveness of Micro, Small and Medium Entrepreneurs during Economic Disruption - Nasser, Alexandria Therese (JPAIR Multidisciplinary Research, 2022)
Micro, small, and medium enterprises (MSMEs) are vital for the progress and growth of most countries’ economies. Globally, there is wide recognition of MSMEs' crucial role as drivers of economic growth and a key source of supplies and support services for major businesses. Hence, a thriving and expanding MSME sector indicates a healthy economy. Compared to larger businesses, they have particular difficulties surviving and expanding amid crises and calamities. Many MSMEs are typically unprepared when unexpected economic disruptions such as disasters and pandemics occur, which prevents them from operating normally. The study used a mixed-methods research design to determine the Competitiveness of Micro, Small, and Medium-sized Enterprises during Economic Disruption. Analyzed data revealed that challenges and opportunities encountered by the MSMEs had an adjectival interpretation of Almost Always or Frequently, indicating that MSMEs experienced both negative and positive, particularly in their businesses. There were lessons learned and best practices experienced by the MSMEs. To overcome these challenges, MSMEs must possess contingency, adaptation, and resilience. Thus, MSMEs should use advantages to be inventive by consistently providing clients with novel and value-adding services to improve their financial performance even during economic disruption.
Keywords: Business and Management; competitiveness; economic disruption; MSMEs; challenges and opportunities; mixed-methods; Philippines